MENA Regional Brief - World Bank (World Bank, Washington, DC, 2016)
The process of political change and transition across much of the Middle East and North Africa (MENA) continued into 2013, with a great degree of heterogeneity across countries. Violence in Syria has escalated, with spillover effects to Lebanon and Jordan. Security in Yemen is fragile but a national dialogue has started which includes the drafting of a new constitution in advance of national elections. In MENA's transitioning countries drafting of new constitutions remains a critical pending issue. Citizens voices continue to be heard across the region calling for greater public participation and open government. The region's main challenge is to create sustainable growth that delivers the quantity and quality of jobs needed. An inclusive and competitive private sector has proven to be one of the most effective and long-term solutions for unemployment, and will be critical in tackling the scale of the problem in MENA.